Perspectives of health practitioners on the challenges to accessing sexual and reproductive health care services for Venezuelan migrant women during the COVID-19 pandemic in Quito, Ecuador - Susana Guijarro; Ana Lucia Torres; Gonzalo Montero; Mónica Garcia; Hernán Sabay; Sarah Iribarren; José Andrés Ocaña; Paula Yánez; Patricio Murgueytio (Pan American Health Organization, 2023)
Objectives. To describe the perspectives of health practitioners on the barriers, gaps, and opportunities that Venezuelan migrant women experienced to accessing sexual and reproductive health (SRH) services during the COVID-19 pandemic and how SRH services were affected in Quito, Ecuador. Methods. Health practitioners involved in SRH services at nine public health care facilities in three zones of Quito were surveyed. The Minimum Initial Service Package readiness assessment tool survey, available from the Inter-Agency Working Group on Reproductive Health in Crisis, was adapted for use and data collection in Ecuador. Results. Of 297 respondents, 227 were included in the analysis. Only 16% of the health practitioners agreed that discrimination against migrant Venezuelans women occurred in the health care system. Of those, only 2.3% described specific conditions associated with discrimination, including requiring identification documents (7.5%) and lack of empathy or responsiveness (6.6%). Most (65.2%) respondents reported that the COVID-19 pandemic affected the use of SRH services by women in the general population and by Venezuelan migrant women more so (56.3%) because of more limited access to SRH services, poverty, and vulnerability. There were no differences between perceptions by levels of health care facility, except with regard to the lack of supplies, awareness of discrimination, and the belief that Venezuelan migrant women were affected more negatively than the local population. Conclusion. The perception among health practitioners in Quito was that discrimination occurred infrequently during the COVID-19 pandemic despite affecting the health care system. However, some level of discrimination toward migrant Venezuelan migrant women seeking SRH services was acknowledged and may be underrepresented.